“Pensando no hoje e no futuro”: iniciativas de mudanças climáticas nas capitais do Nordeste do Brasil - Rylanneive Leonardo Pontes Teixeira; Rafael Aguiar da Silva; Ana Luiza Fontenelle; Yonara Claudia dos Santos; Zoraide Souza Pessoa (Confins)
In Brazil, the Northeast region is highly vulnerable to climate change due to its low rates of socioeconomic development. Based on this assumption, we aim to investigate how the capitals of the Brazilian Northeast have internalized the climate issue in their local government agendas, identifying and analyzing the initiatives aimed at tackling climate change at the local level. For this, anchored in a qualitative methodology, we make use of bibliographic survey, as well as analysis of documents and journalistic news, analyzed from the content analysis technique. The analysis and discussion show the local governments' inefficiency to deal with climate change. In summary, we conclude that climate issues are internalized and implemented at different levels in the government agendas of the cities analyzed, with the majority of them presenting low incorporation.